Tanggapan Tokoh Agama Kabupaten Aceh Utara tentang Hak Istri Menolak Rujuk Suami menurut Hukum Islam dan Hukum Positif: Hak Istri Menolak Rujuk Suami - Hanafiah, Mahmudi (Al-Mizan, 2024)
This study examines the polemic between Islamic law according to the Shafi'i school and positive law regarding a wife's right to reject reconciliation (rujuk) in North Aceh Regency. Positive law grants a wife the right to object to her husband's intention to reconcile through a formal mechanism, while the Shafi'i school states that reconciliation is valid without the wife's consent during the iddah period of revocable divorce (talak raj’i). This discrepancy raises questions within the religious social practices of Acehnese society, which consistently adheres to the Shafi'i school. This research aims to analyze the perspectives of religious leaders in North Aceh regarding a wife's right to reject reconciliation under Islamic law and positive law. Using a qualitative method, data were collected through field observations and interviews with local religious leaders. The findings reveal that religious leaders support the Shafi'i perspective, which asserts that reconciliation is the husband's absolute right. A wife's objection to reconciliation is considered an act of disobedience (nusyuz) that does not annul the marriage but impacts her rights, such as financial maintenance (nafaqah). Moreover, a wife who refuses reconciliation remains legally bound to her husband under Islamic law if the husband has pronounced a valid reconciliation statement. This study underscores the importance of harmonizing positive law and Islamic law to maintain social harmony in Aceh.